(untitled) (Journal SCIENCEVOLUTION, 2022)
Public administration confronts ongoing challenges in modernization and human resource management, requiring enhanced public servant competencies for efficient governance. This study designs a Sustainable Strategic Plan to advance professional development among public servants at Chiclayo Provincial Municipality, using a quantitative, non-experimental descriptive-project design with 62 employees from its Road Development and Transportation Management Office. Results highlight the need for improvedtraining and professional development. While 55% strongly agreed on instrument effectiveness, 44% on strategy, 47% on process, and 44% on performance, 45% strongly disagreed with work quality/efficiency, and 35% with outstanding performance. It is imperative to implement strategic planning policies that incorporate leadership training, communication skills, and personal development programs to strengthen organizational culture. These measures aim to address identified gaps and align workforce competencies with institutional objectives, fostering a more effective and motivated public service framework.